Metodologia de planejamento técnico de redes de distribuição de energia elétrica em cenários de elevada penetração de geração distribuída - Donadel, Clainer Bravin (2015)
Distribution Network Operators (DNOs) have their performance evaluated by economic indicators according to their technical planning process. The methodologies adopted have been restructured and improved over the years due to gradual implementation of the Smart Grid philosophy and distributed generation units (DGs) connections. However, there are few DNOs around the world that consider the influence of Smart Grid philosophy and DGs connections in their technical planning methodologies. Therefore, in a medium-term, DNOs should improve their technical planning methodologies in order to suit the new scenario. Thus, this thesis proposes the development of conceptual bases in order to adapt technical and regulatory aspects of technical planning methodologies, covering two main problems found in the literature: DG operations in a Pre Smart Grid environment, which does not consider that the Smart Grid philosophy is completely implemented; and the optimal placement of DGs in electrical distribution networks. The major contribution of this thesis is the proposition of solutions for the two problems previously mentioned, according to which, technical planning methodologies need to be improved.